Toys for the boys?: drones, pleasure and popular culture in the militarisation of policing - Salter, Michael (Critical criminology, 2014)
This paper argues that the various and contradictory rationales offered for law enforcement drones are symptomatic of a ‘weapons fetish’ evident in popular culture. This fetishisation imbues military technology such as the drone with masculine fantasies of control and domination that obscure the practical limitations and ethical implications of drones for crime control and prevention. By linking the pleasures of militarism to crucial shifts in the social and economic order, the paper argues that counter-terrorism discourse functions to legitimate the militarised masculine subject positions of paramilitary policing specifically and the neoliberal state generally. In such a context, the drone features as a regressive ‘weapon-toy’ that fuses state control with technological transcendence.